2013
DOI: 10.1902/jop.2012.120415
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Collagen Membrane Loaded With Recombinant Human Bone Morphogenetic Protein‐2 With Collagen‐Binding Domain for Vertical Guided Bone Regeneration

Abstract: The present study demonstrates that CMs loaded with small doses of rhBMP-2/CBD induce new bone formation not only from the surface of the native bone, but also from the superficial structures. The augmented new bone, therefore, is improved in both quantity and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In vivo animal experiments have compared the bone regenerative effects of native membranes and membranes immobilized or loaded with recombinant human BMP‐2 (rhBMP‐2) (Shim et al., ), rhBMP‐2 with a collagen‐binding domain (Lai, Zhou, Wang, Lu, & Gao, ), BMP‐7 (Jo et al., ), a combination of BMP‐2 and BMP‐7 (Jo et al., ), bFGF/FGF‐2 (Lee et al., ), FGF‐2 (Hong et al., ), PDGF (Park, Ku, Chung, & Lee, ) and bone‐forming peptide‐1 (BFP1) (Lee et al., ) (a peptide sequence from the immature region of BMP‐7) (Kim et al., ) (examples are provided in Table ). Most experimental in vivo studies have been performed with degradable membranes/materials in rodent calvarial defects.…”
Section: Results Of the Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo animal experiments have compared the bone regenerative effects of native membranes and membranes immobilized or loaded with recombinant human BMP‐2 (rhBMP‐2) (Shim et al., ), rhBMP‐2 with a collagen‐binding domain (Lai, Zhou, Wang, Lu, & Gao, ), BMP‐7 (Jo et al., ), a combination of BMP‐2 and BMP‐7 (Jo et al., ), bFGF/FGF‐2 (Lee et al., ), FGF‐2 (Hong et al., ), PDGF (Park, Ku, Chung, & Lee, ) and bone‐forming peptide‐1 (BFP1) (Lee et al., ) (a peptide sequence from the immature region of BMP‐7) (Kim et al., ) (examples are provided in Table ). Most experimental in vivo studies have been performed with degradable membranes/materials in rodent calvarial defects.…”
Section: Results Of the Literature Surveymentioning
confidence: 99%
“…Most experimental in vivo studies have been performed with degradable membranes/materials in rodent calvarial defects. Compared with native membranes, membranes immobilized or loaded with these different growth factors/peptides demonstrate increased in vivo bone regeneration (Hong et al., ; Jo et al., ; Lai et al., ; Lee et al., , ; Park et al., ; Shim et al., ) (Table ). Moreover, a polycaprolactone (PCL)/gelatin membrane functionalized with CXCL12/SDF‐1α, which stimulated bone marrow stromal cell (BMSC) chemotaxis in vitro , promoted a sixfold increase in bone formation compared to that afforded by the native membrane after 8 weeks in vivo (Ji et al., ).…”
Section: Results Of the Literature Surveymentioning
confidence: 99%
“…Overall, experimental studies suggested that, although different growth factors (namely PDGF‐BB, FGF‐2, VEGF) may positively influence bone formation, BMP‐2 seems the most effective for the regeneration of cranial and maxillofacial defects and de novo bone formation, regardless of the carrier adopted. Remarkably, some experimental studies suggested that it might enhance GBR‐induced bone regeneration (Du et al., ; Huang et al., ) and de novo bone formation (Lai et al., ; Lee et al., ). rhBMP‐2 also showed to support post‐extraction alveolar bone regeneration and ridge augmentation in chronic and combined acute‐chronic defects, but while ACS could be successfully used as a carrier for inlay purposes, space‐providing materials should be preferred for onlay purposes (Barboza et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The other main difference between these two studies-apart from the healing period-was in the type of carrier material used. Various carrier materials have been used for rhBMP-2 [25][26][27]. It was speculated that using a CM as a carrier for rhBMP-2 could enhance the osteoinductivity of the periosteum due to the close proximity of the membrane and the periosteum.…”
Section: Discussionmentioning
confidence: 99%